DEVELOPMENT OF THE CULTURAL AND LEISURE SPHERE IN THE MOSCOW - N. N. Musinova (Вестник университета, 2021)
The article substantiates the special significance of the development of the cultural and leisure sphere for the city of Moscow. The paper describes the organization of its management system. The author presents the results of the analysis of the main directions of the development of the cultural and leisure policy of the city of Moscow in three components: content,  infrastructure and territorial. The issues of providing the services of cultural and leisure facilities to the residents of the peripheral territories of the city of  Moscow are of paramount importance at the present time. At the same time, the study notes the peculiarities of creating conditions for organizing leisure activities and providing residents with cultural services in the context of the COVID-19 pandemic. The author identifies the most significant shortcomings that hinder the further development of cultural and leisure activities in the territory of the city of Moscow and determines the main directions of its further development.